Theoretical concepts and practice of community organizing - Dizon, Josefina T. (2012)
Community organizing, one of the methods in community development, is a Western concept adopted in the Philippines. The different definitions of foreign and local authors highlight the nature of community organizing as a process by which a community identifies its problems and finds solutions through collective mobilization of the people and resources. The paper discusses the theoretical concepts of community organizing, which include its ideological background and value orientations, assumptions and propositions, goals, approaches, and principles. Towards the end, the paper discusses the steps involved in community organizing and forwards a conceptual framework of community orginizing focused on people empowerment and based on the concept of people-centered participatory development.
Keywords: Community organization; People empowerment